If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -2 = -4c + 8x Reorder the terms: -2 + 6x = -4c + 8x Solving -2 + 6x = -4c + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -2 + 6x + -8x = -4c + 8x + -8x Combine like terms: 6x + -8x = -2x -2 + -2x = -4c + 8x + -8x Combine like terms: 8x + -8x = 0 -2 + -2x = -4c + 0 -2 + -2x = -4c Add '2' to each side of the equation. -2 + 2 + -2x = 2 + -4c Combine like terms: -2 + 2 = 0 0 + -2x = 2 + -4c -2x = 2 + -4c Divide each side by '-2'. x = -1 + 2c Simplifying x = -1 + 2c
| 180x+x=180 | | 2(2-x)=8-2(2-x) | | f(x)=(15x) | | y+16=20 | | 90x+x=180 | | 10-.25x=.5+4 | | 4(v+5)+8v=32 | | x^2-10x-27=0 | | x-76y=0 | | 12x^2+6x+82=0 | | 4x^2-5sinx=0 | | -5n-3n+2=34 | | 18x-6=-10 | | 4x^2-5sinx= | | (6+u)(3u+4)=0 | | (27x)27=21(21+2x+8) | | 2(2-x)=8-2(-x) | | ln(6)+ln(x)=4 | | 2x+3(2+5)=X | | 4(3x^2+2x)-12x^2=2(8x+6) | | 4x+3(x-6)=-11 | | -6-(21-6X)=-51+2X | | 4x-9y+6x+3y-2x=0 | | 3(2x-6)-(2x+1)=9 | | 2x+1=3(x-1) | | 5x-3x=x+9 | | 8n=5n+39 | | 7.4=w-3.9 | | 33=7(w+7)-3w | | n-37=0 | | 150=v+113 | | sqrt(x+1)-sqrt(9-x)=sqrt(2x-12) |